Answer :

Given: m1= 1kg, m2= 2kg, m3=3kg

For m1 to be at rest, a1 = 0.

T − m1 g = 0

T = m 1g …(i)

For mass m2, − 2g = 2a

T = 4a + 4g …(ii)

For mass m3, 3g – = 2a

T = 6g − 6a

From equations (ii) and (iii), we get:

3T – 12g = 12g – 2T

T = = 4.08g

Substitute the value of T in equation (i), we get: m1 = 4.8kg

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses

A rectangular boxPhysics - Exemplar

A helicopter of mPhysics - Exemplar

There are four foPhysics - Exemplar

When a body <spanPhysics - Exemplar

Block <span lang=Physics - Exemplar

A block <span lanPhysics - Exemplar

Two <span lang="EPhysics - Exemplar